FIXED POINT THEOREMS FOR ĆIRIĆ’S QUASICONTRACTION IN GENERALIZED COMPLEX VALUED METRIC SPACES - Yuying, T.; Inchan, I.; Rattanaseeha, K. (Journal of Nonlinear Analysis and Optimization: Theory & Applications (JNAO), 2024)
In this work, we introduce some property of the generalized complex valued metric space and we extend some fixed point results thai is Ćirić’s fixed point theorem. Some are recover various complex valued metric space and complex valued b-metric space. Our results extended and improve some results of Mohamed Jleli and Bessem Samet [17].